Adolescents' smokeless tobacco susceptibility by perceived professional baseball players' use. (7th June 2017) - Chaffee, Benjamin W.; Couch, Elizabeth T.; Gansky, Stuart A.
Abstract: Objective: Measure associations between adolescent baseball players' perceptions of smokeless tobacco (ST) use by professional baseball players and those adolescents' actual ST use and susceptibility. Methods: Male baseball players ( N = 360) at 25 rural California high schools completed tobacco behavior surveys and reported how likely they believed it was their favorite major league baseball player used ST. We compared ST use and, among ST never‐users, willingness and expectations to use ST, according to perceived favorite player's use. Results: Adolescents responding that their favorite player definitely or probably used ST were significantly more likely to use ST themselves. High school ST never‐users who perceived that their favorite player definitely used ST were 2.5 to 3‐times more likely to be susceptible to ST initiation than participants responding that their favorite player definitely did not use ST. Conclusions: Adolescents' ST behaviors and intentions were correlated with their perceptions of professional baseball players' ST use.